Insecticidal activity of an essential oil of Tagetes patula L. (Asteraceae) on common bed bug Cimex lectularius L. and molecular docking of major compounds at the catalytic site of ClAChE1 - Politi, Flávio Augusto Sanches [UNESP]; Nascimento, Juliana Damieli [UNESP]; da Silva, Alexander Alves [UNESP]; Moro, Isabela Jacob [UNESP]; Garcia, Mariana Lopes; Guido, Rafael Victório Carvalho; Pietro, Rosemeire Cristina Linhari Rodrigues [UNESP]; Godinho, Antônio Francisco [UNESP]; Furlan, Maysa [UNESP] (Springer Nature, 2017)
Emerging resistance to insecticides has influenced pharmaceutical research and the search for alternatives to control the common bed bug Cimex lectularius. In this sense, natural products can play a major role. Tagetes patula, popularly known as dwarf marigold, is a plant native to North America with biocide potential. The aim of this work was to evaluate the biological activity of T. patula essential oil (EO) against adult common bed bugs via exposure to dry residues by the Impregnated Paper Disk Test (IPDT) using cypermethrin as a positive control. We selected the enzyme acetylcholinesterase as a target for modeling studies, with the intent of investigating the molecular basis of any biological activity of the EO. Chemical analysis of the EO was performed using gas chromatography coupled to mass spectrometry (GC-MS). Additionally, oral and dermal acute toxicity tests were performed according to Organization for Economic Cooperation and Development (OECD) guidelines. The sulforhodamine B assay (SRB) was performed to verify the cytotoxicity of EO to HaCaT cells. The EO eliminated 100 % of the bed bugs at 100 mg mL−1 with an LC50 value of 15.85 mg mL−1. GC-MS analysis identified α-terpinolene, limonene, piperitenone, and piperitone as major components of the mixture. Molecular modeling studies of these major compounds suggested that they are acetylcholinesterase inhibitors with good steric and electronic complementarity. The in vitro cytotoxicity evaluation revealed a LC50 = 37.06 μg mL−1 and in vivo acute toxicity showed an LC50 >4000 mg kg−1, indicating that the EO presents low risk of toxic side effects in humans. The T. patula essential oil components provide a promising strategy for controlling bed bug populations with low mammalian toxicity. These findings pave the way for further in vivo studies aimed at developing a safe and effective insecticide.
Keywords: Acetylcholinesterase inhibitors; Homology modeling; Insecticide resistance; Natural products